MANAJEMEN ZAKAT PRODUKTIF DALAM PERSPEKTIF UNDANG-UNDANG ZAKAT NOMOR 23 TAHUN 2011 (AL MUNAZHZHARAH, 2020)
Productive Zakat is zakat given in the form of productive goods, where by using these goods it can create a business such as a sewing machine or be realized in the form of a revolving capital grant, both for capital of social projects, such as the construction of schools, health facilities or places worship. By making productive use of zakat assets, it means that zakat assets not only help reduce the burden on the poor, but also help reduce unemployment in Indonesia. Based on the description above, researchers are interested in researching about "Productive Zakat Management in Perspective of the Zakat Law Number 23 of 2011. This study uses qualitative methods that describe the results and discussion of research with descriptive analytical methods. Productive zakat management in its implementation there are provisions in Article 1 of the zakat Law explaining that as planned, it must have the aim of increasing the standard of living and welfare of the community in its organization having provisions in Article 36 where the productive utilization of zakat is regulated by BAZNAS.